Discursive intersexions : daring bodies between myth, medicine, and memoir - Koch, Michaela (Praktiken der Subjektivierung, 2017)
Life narratives and fiction that represent experiences of hermaphroditism and intersex are at the core of Michaela Koch's study. The analyzed texts from the 19th to the early 21st century are embedded within and contrasted with contemporary debates in medicine, psychology, or activism to reveal the processes of negotiation about the meaning of hermaphroditism and intersex. This cultural studies-informed work challenges both strictly essentialist and constructivist notions. It argues for a differentiated perspective on intersex and hermaphrodite experiences as historically contingent, fully embodied, and nevertheless discursive subject positions.